Otoferlin as a multirole Ca2+ signaling protein: from inner ear synapses to cancer pathways - Leclère, Jean-Christophe; Dulon, Didier (Frontiers in Cellular Neuroscience, 2023)
Otoferlin, a protein mainly found in the inner ear and the brain, is essential for hearing, and mutations in OTOF cause severe to profound deafness. This protein is a member of the ferlin family, which shares several common properties, including the ability to bind calcium and interact with membrane phospholipids. This review provides an overview of the otoferlin molecular structure, its isoforms, its essential role in transducing soundsignals into nerve impulses, and current treatment modalities for otoferlin-related deafness. Recent publications discussing potential improvements in treatment, particularly in the area of gene therapy, are also covered. Clinical trials have just begun in 2022, following several publications showing restoration of hearing in mice treated with viral vector-based gene therapy. Recent studies have also shown interest in otoferlin as a prognostic marker in several types of cancer, likely related to its role in membrane fusion. Mechanisms need to be explored, and this review provides a general understanding of the current knowledge of this protein. Advances in gene therapy for the inner ear could also benefit from this area of research and potentially lead to improved treatments for these cancers.